The role of allogeneic platelet-rich plasma in patients with diabetic foot ulcer: Current perspectives and future challenges - He, Min; Chen, Tianyi; Lv, Yuhuan; Song, Peiyang; Deng, Bo; Guo, Xuewen; Rui, Shunli; Boey, Johnson; Armstrong, David G.; Ma, Yu; Deng, Wuquan (Frontiers in Bioengineering and Biotechnology, 2022)
The frequency of chronic cutaneous wounds are sharply increasing in aging populations. Patients with age-related diseases, such as diabetes, tumors, renal failure and stroke are prone to soft tissue and skin injury, compounded by slowed healing in aging. Imbalance of wound inflammation, loss of growth factor secretion, and impairment of tissue repair abilities are all possible reasons for failed healing. Therefore, it is vital to explore novel approaches to accelerate wound healing. Platelet-rich plasma (PRP) as a cell therapy has been widely applied for tissue repair and regeneration. PRP promotes wound healing by releasing antimicrobial peptides, growth factors and micro-RNAs. Medical evidence indicates that autologous platelet-rich plasma (au-PRP) can promote wound healing effectively, safely and rapidly. However, its clinical application is usually restricted to patients with chronic cutaneous wounds, generally because of other severe complications and poor clinical comorbidities. Allogeneic platelet-rich plasma (al-PRP), with abundant sources, has demonstrated its superiority in the field of chronic wound treatment. Al-PRP could overcome the limitations of au-PRP and has promising prospects in clinical applications. The aim of this review is to summarize the current status and future challenges of al-PRP in chronic cutaneous wound management. We also summarized clinical cases to further describe the application of al-PRP for chronic wounds in clinical practice.